Influence of Videogames on Student Behavior - Carolina Meneses Quimis, Ivonne; Elena Moya Martínez , María; Rodríguez Gámez, María (International Journal of Psychosocial Rehabilitation, 2020)
For a few decades, new technologies have evolved in such a way that the current generations since birth are impregnated with a different culture from earlier times, this seen from various environments. Visual and sensory development increases in these processes where it can be linked to brain development, if we compare it with other generations, it shows how this learning process is faster. Bibliographic analysis from different dimensions has allowed us to know the link between the application of video games and the teaching-learning process, which is used as a teaching resource in the formation of new knowledge that contributes to the acquisition of information. The excessive handling of these virtual applications can cause health problems; such as sedentary lifestyle, anxiety, obesity, or physical malformations due to posture, thus altering the normal lifestyle of the video player and his family. Video games influence the behavior of children, depending on the social environment where they develop as they are the school, their family and their implicit characteristics of their personality, in this environment teachers and parents are responsible for controlling the use of children. Electronic devices and games according to their needs because they can cause disorders in different scenarios, due to lack of control or emotional problems.